J.P. Doodles inhabits Range (Raton, NM Raton Range, 1992)
This article is about the newspaper cartoon J.P Doodles being carried by the Raton Range.
Newspaper article + Doodle
Mater List Item # 42
File location is in the New Mexico File Cabinets
Keywords: McWilliams, Barry; J. P. Doodles; Newspaper Cartoons; Funny Pages; Cartoon Strips; Funnies; Syndicates; Cimarron, New Mexico